2021
DOI: 10.1037/tam0000166
|View full text |Cite
|
Sign up to set email alerts
|

An epidemiological analysis of public mass shooters and active shooters: Quantifying key differences between perpetrators and the general population, homicide offenders, and people who die by suicide.

Abstract: This study compared public mass shooters (n = 171) and active shooters (n = 63) in the United States to the general population, homicide offenders, and people who die by suicide. Comparisons with the general population are the foundation of epidemiological research, and comparisons with homicide offenders and people who die by suicide are helpful because public mass shooters and active shooters always intend to kill and often take their own lives. Findings indicate that public mass shooters were more often mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…Contrary to Lankford et al's (2021) hypotheses, mass shooters did not possess firearms or have prior felony convictions at higher rates than the average American. Mass shooters were more likely to have admitted or exhibited suicidal ideation and to have a lifetime thought disorder diagnosis than the general population (Lankford et al, 2021); however, past mental health diagnoses were significantly more common in POC than active shooters (Gibson et al, 2020;Meloy et al, 2019), and the two groups show similar rates of prior suicidal behavior (Gibson et al, 2020).…”
Section: Differentiating Active Shooters and Pocmentioning
confidence: 91%
See 1 more Smart Citation
“…Contrary to Lankford et al's (2021) hypotheses, mass shooters did not possess firearms or have prior felony convictions at higher rates than the average American. Mass shooters were more likely to have admitted or exhibited suicidal ideation and to have a lifetime thought disorder diagnosis than the general population (Lankford et al, 2021); however, past mental health diagnoses were significantly more common in POC than active shooters (Gibson et al, 2020;Meloy et al, 2019), and the two groups show similar rates of prior suicidal behavior (Gibson et al, 2020).…”
Section: Differentiating Active Shooters and Pocmentioning
confidence: 91%
“…Distinguishing between attackers and POC, whose behavior caused concern but who did not subsequently engage in violence, has proven even more challenging. For example, an epidemiological analysis of mass shooters found they were more likely to be unemployed, unmarried, and have military experience than the general population (Lankford et al, 2021), but it is not clear these demographic differences persist when compared with POC. Meloy et al (2019) found terrorist attackers were less likely to be married than POC but observed no significant difference in employment status.…”
Section: Differentiating Active Shooters and Pocmentioning
confidence: 99%
“…In terms of public mass shootings, previous studies have examined differences between blue-and white-collar perpetrators (Peterson & Densley, 2019;Silva, 2019;Silva & Greene-Colozzi, 2019), as well as employed and unemployed shooters (Lankford et al, 2021;Pah et al, 2017). While previous research has included military history as a variable of interest (Silva, 2021;Silva & Greene-Colozzi, 2021b), there is a dearth of research exploring an association been a specific occupation (e.g., military) and rates of casualty in public mass shootings.…”
Section: Military Historymentioning
confidence: 99%
“…Most notably, public mass shooters are almost always male (Duwe, 2020). They also tend to be young (Lankford et al, 2021). In addition, approximately 80% of perpetrators are unmarried when they attack, and they appear unlikely to have children (Peterson & Densley, 2021).…”
Section: Public Mass Shooters and Sexual Frustrationmentioning
confidence: 99%
“…In addition, approximately 80% of perpetrators are unmarried when they attack, and they appear unlikely to have children (Peterson & Densley, 2021). Finally, public mass shooters are more likely to be unemployed than the average American (Lankford et al, 2021). Overall, this suggests that being young, male, unmarried, childless, and unemployed may be associated with both sexual frustration problems and public mass shootings.…”
Section: Public Mass Shooters and Sexual Frustrationmentioning
confidence: 99%